Innovative Marketing of Traditional Thai Luk Chup as a Healthy Snack Option - Tiffany, Evellyn Try; Aripradono, Heru Wijayanto (International Journal of Economics Development Research (IJEDR), 2024)
In the development of the 4.0 technology industry, many people realize the importance of healthy living through the internet media. Researchers conducted observations in the field of digital marketing business. Balanced with increasingly sophisticated technology, the level of public awareness is also increasing. This is illustrated by the large number of people sharing sports content and healthy food preparations. This kind of lifestyle is also widely found in Batam City. Through observation, researchers found that 7 out of 10 people choose to live with a good pattern. However, many of them complain that it is difficult to get healthy food in Batam City. Researchers are motivated to create innovations to help people who choose a healthy lifestyle. Designing the Scottytasty Instagram account by offering Thai snack products, namely Lok chup. Food processed with various forms of fruit with green bean filling makes healthy consumers easy to consume. This study uses a qualitative research method with a Design Thinking stage approach to healthy food consumers. Design thinking has several stages in its work, namely empathy, definition, idea, prototype, and testing. Through these stages, researchers can combine creative and critical thinking that allows information and ideas to be organized, decisions to be made, situations to be improved, and knowledge to be gained. This research is expected to help people with a healthy lifestyle easily access healthy food and help in the marketing strategy process, especially in the digital era.